Β-arrestin-2 alleviates rheumatoid arthritis injury by suppressing NLRP3 inflammasome activation and NF- κB pathway in macrophages. Issue 1 (1st January 2022) - Cao, Feng; Huang, Cheng; Cheng, Jiwei; He, Zhaochun
ABSTRACT: Rheumatoid arthritis (RA) is a chronic inflammatory joint disorder that inflicts damage to the joints of the hands and wrist. The aim of this study was to investigate the protective effect of β-Arrestin-2 (βArr2) on RA in vivo and in vitro . The βArr2 adenovirus (βArr2-Ad) or the control (Con-Ad) was injected into the ankle joint cavity of collagen-induced arthritis (CIA) mice. According to the results, an improvement was shown in the symptoms and pathological injury of RA after an upregulation of βArr2. Correspondingly, the inflammatory response was attenuated, as evidenced by the decreased serum pro-inflammatory cytokines levels and NF-κB pathway-related proteins. Nucleotide-binding domain leucine-rich repeat and pyrin domain containing receptor 3 (NLRP3) inflammasome activation was inhibited in CIA mice treated with βArr2-Ad injection, as reflected by the diminished IL-18 level and declined protein levels of inflammasome components in the ankle joint. Likewise, the anti-inflammatory effect of macrophages was also validated by in vitro experiments. In summary, βArr2 effectively ameliorates ankle inflammation in CIA mice via NF-κB/NLRP3 inflammasome, providing theoretical and clinical basis for RA therapy.